A Study of Attitudes and Affecting factors for Purchasing Herbal Cosmetics in Undergraduate Group in Phitsanulok Province to Penetrate the New Customers Group - Sae-lee, Phetcharayud; Wichitphongsa, Wachira; Puongyaem, Hathaithanok (Humanities and Social Sciences Journal of Pibulsongkram Rajabhat University, 2021)
This research studied the attitudes and affecting factors for purchasing herbal cosmetics in undergraduate group in Phitsanulok province. Logit model was built and used to predict the decisions. We proposed guidelines for developing herbal cosmetic products in accordance with the needs of undergraduate group. The results, found that most of them like to buy cosmetics from department stores and convenience stores and spend 501-1,000 Baht per month to buy cosmetics, most students have used herbal cosmetics before. The most marketing mix factors that affected by their decision to buy herbal cosmetics is the factors of production, which must be the products with standard quality, safe and certified by relevant agencies. The results from logit model showed the most personal affecting factors were gender, experience of using herbal cosmetics and educational institutions respectively, And the most marketing mix factors that affect to the students’ decision were the receipt number, brand, packaging and promotion, respectively. The Logit model can be used to predict the decision of herbal cosmetics purchasing for undergraduate group with correctly predicted values 77.65%.